2014
DOI: 10.4055/cios.2014.6.4.432
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Fractures in Non-Accidental Injuries in the Pediatric Population in Singapore

Abstract: BackgroundFractures as a result of non-accidental injuries (NAI) are not uncommon among children. The purpose of our study was to describe the incidence, demographic characteristics, and associated risk factors in patients with NAI in a multiethnic Asian cohort.MethodsA retrospective record review of patients admitted to our hospital between September 2007 and 2009 with the diagnosis of NAI was conducted.ResultsA total of 978 children were reported with suspicion of NAI. Among them, 570 patients (58.28%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…The prevalence of specific fracture sites associated with NAT varies greatly throughout the literature, primarily in regard to all fractures versus fracture patterns treated by orthopaedic surgeons (ie, extremity, vertebral, and pelvic fractures). 7,10,11,[14][15][16] Our fracture site prevalence among children with child abuse closely approximates the distribution reported by Gera et al and Valvano et al 7,16 We noted that the mortality rates doubled when the fracture had been identified as a result of NAT. Upper limb fractures demonstrated the greatest association with the risk of death when the hospital admission had also been coded for child abuse (OR = 6.3, P , 0.0001).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of specific fracture sites associated with NAT varies greatly throughout the literature, primarily in regard to all fractures versus fracture patterns treated by orthopaedic surgeons (ie, extremity, vertebral, and pelvic fractures). 7,10,11,[14][15][16] Our fracture site prevalence among children with child abuse closely approximates the distribution reported by Gera et al and Valvano et al 7,16 We noted that the mortality rates doubled when the fracture had been identified as a result of NAT. Upper limb fractures demonstrated the greatest association with the risk of death when the hospital admission had also been coded for child abuse (OR = 6.3, P , 0.0001).…”
Section: Discussionsupporting
confidence: 86%
“…Whether performing a consultation in the emergency department or an inpatient setting, orthopaedic surgeons are trained to recognize certain fracture patterns as indicators of NAT; however, the association of these indicators has not been well quantified for clinical use. [7][8][9][10][11] The Kids' Inpatient Database (KID) is part of a larger collection of databases organized and funded by the Agency for Healthcare Research and Quality. 12 It is a unique allpayer database that collects comprehensive information on pediatric (age , 21 years) hospital admissions on a national scale.…”
mentioning
confidence: 99%
“…Our results indicate that physical abuse of children younger than three years was undoubtedly confirmed in only 5% of 98 suspected cases. This is relatively low compared to other reports because there was no consistent approach to the investigation of these children [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 60%
“…Large studies cite unknown or inconsistent history of mechanism of injury as a major indicator of abuse [1,2,3,[15][16][17][18][19][20]. In most of our cases, the mechanism of injury was either unknown or it was stated to be self-injury.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation